To Sign or Not to Sign? The Impact of Encouraging Infants to Gesture on Infant Language and Maternal Mind‐Mindedness. Issue 2 (3rd October 2012) - Kirk, Elizabeth; Howlett, Neil; Pine, Karen J.; Fletcher, Ben (C)
<x xml:space="preserve">Abstract</x> Findings are presented from the first randomized control trial of the effects of encouraging symbolic gesture (or "baby sign") on infant language, following 40 infants from age 8 months to 20 months. Half of the mothers were trained to model a target set of gestures to their infants. Frequent measures were taken of infant language development and dyadic interactions were scrutinized to assess mind‐mindedness. Infants exposed to gesture did not differ from control conditions on language outcomes; thus, no support was found for previous claims that encouraging gesturing with infants accelerates linguistic development. Microgenetic analysis revealed mothers in the gesture training conditions were more responsive to their infants' nonverbal cues and encouraged more independent action by their infant.